Conductive mortar and preparation method thereof and auxiliary anode material
By adding carbon materials, fly ash and ore powder to the conductive mortar, building a conductive grid and performing secondary hydration, the problem that conductive mortar cannot effectively resist auxiliary anode acidification, and achieving efficient acidification and long-term protection of conductive mortar.
Patent Information
- Application Number
- CN202310165643.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-16
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2043-02-16
AI Technical Summary
The existing conductive mortar cannot effectively resist the acidification of the auxiliary anode, resulting in the gradual loss of the protection function of the cathode protection system.
Conductive mortar based on cement and sand and gravel is used, and a macroscopic or microscopic conductive grid is constructed by adding carbon materials, fly ash and ore powder to the cement mortar, and secondary hydration is carried out during the cement hydration process to improve the density and mechanical properties of the material.
By reducing the resistivity of the conductive mortar and improving its mechanical properties, the anti-acidification ability of the conductive mortar to the auxiliary anode is significantly improved, and the service life of the cathode protection system is extended.
Smart Images

Figure CN116253548B_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of protective materials for construction projects, and in particular relates to a conductive mortar and a preparation method thereof, and an auxiliary anode material. Background Art
[0002] The principle of cathodic protection technology (ICCP) is to use impressed current to shift the potential of steel bars to the protective potential, so that the steel bars are in a protective state and avoid corrosion. It is one of the main means to achieve corrosion protection of steel bars in coastal tidal range and splash zones. However, since the auxiliary anode in the cathodic protection system is in a polarized state for a long time, as the protection progresses, the OH in the pore solution of the external anode - Continuous consumption will reduce the alkalinity of the pore solution, causing the phenomenon of "calcium dissolution", which will lead to continuous acidification of the auxiliary anode, increase the resistivity, and uneven distribution of the protection current, which may eventually cause the ICCP system to lose its protection function. Therefore, solving the problem of auxiliary anode acidification is the key to achieving long-term normal service of the ICCP system.
[0003] At present, the commonly used auxiliary anode materials are mainly formed by conductive cement mortar. The conductive materials in conductive cement mortar mainly include graphite powder, steel chips, steel fibers, carbon fibers, carbon nanotubes and graphene. Although the conductive properties of these conductive materials can be used to construct "conductive grids" of different sizes in cement mortar, the conductive paths formed by multi-sized "conductive grids" can reduce the resistivity, thereby achieving the purpose of cathodic protection. However, these conductive materials cannot slow down OH when constructing conductive grids. - Consumption cannot prevent calcium dissolution.
[0004] Therefore, it is necessary to propose a conductive mortar that can both reduce the resistivity of cement mortar and improve the acidification resistance of the auxiliary anode. Summary of the invention
[0005] The purpose of the present application is to provide a conductive mortar and a preparation method thereof and an auxiliary anode material, aiming to solve the problem that the existing conductive mortar cannot resist the acidification of the auxiliary anode.
[0006] In order to achieve the above application purpose, the technical solution adopted in this application is as follows:
[0007] In a first aspect, the present application provides a conductive mortar, which comprises the following components in percentage by weight, based on the total weight of the conductive mortar being 100%:
[0008]
[0009] In a second aspect, the present application provides a method for preparing a conductive mortar, comprising the following steps:
[0010] Providing various raw material components in the conductive mortar of the present application;
[0011] The carbon material is dispersed and then dried to obtain a dispersed carbon material;
[0012] Performing a first mixing process on the dispersed carbon material and sand and gravel to obtain a first mixture;
[0013] Performing a second mixing process on the first mixed material, cement, fly ash and mineral powder to obtain a second mixed material;
[0014] The second mixture and water are subjected to a third mixing process to obtain a conductive mortar.
[0015] In a third aspect, the present application provides an auxiliary anode material, which is formed by the conductive mortar of the present application, or the conductive mortar prepared by the preparation method of the conductive mortar of the present application.
[0016] Compared with the prior art, this application has the following beneficial effects:
[0017] The conductive mortar provided in the first aspect of the present application is based on cement and sand and gravel, and is synergistically combined with carbon materials, fly ash and mineral powder. Not only can macroscopic or microscopic conductive grids be constructed inside the cement mortar through carbon materials, fly ash and mineral powder, but conductive grids of multiple sizes can jointly build conductive paths to reduce the resistivity of the conductive mortar. Moreover, the coordinated use of carbon materials, fly ash and mineral powder can be secondary hydrated during the cement hydration process, thereby improving the density and mechanical properties of the conductive mortar material. At the same time, fly ash and mineral powder can also be effectively filled into the pores of the conductive mortar or concrete during the secondary hydration, thereby reducing the intrusion of chloride ions into the cement, thereby reducing OH ﹣ consumption, thus improving the ability of the conductive slurry to resist auxiliary anodic acidification.
[0018] The second aspect of the present application provides a method for preparing a conductive mortar. In the first step, the carbon material is dispersed to fully disperse the carbon material to obtain a dispersed carbon material. In the second step, the dispersed carbon material is mixed with sand and gravel to obtain a first mixture. In the third step, the first mixture is mixed with cement, fly ash and mineral powder to obtain a second mixture. Finally, the second mixture is mixed with water to obtain a conductive mortar. The preparation method is simple and convenient, does not require large-scale instruments and equipment, and is conducive to large-scale application.
[0019] The auxiliary anode material provided in the third aspect of the present application is formed by the conductive mortar of the present application, or the conductive mortar prepared by the preparation method of the conductive mortar of the present application. Therefore, the auxiliary anode material of the present application has excellent conductive properties, mechanical properties and acid resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0021] Figure 1 This is a schematic diagram of an acid resistance test of the conductive mortar provided in an embodiment of the present application;
[0022] Figure 2 It is a schematic diagram of the resistivity test using the four-electrode method for conducting conductivity test on the conductive mortar provided in the embodiment of the present application. DETAILED DESCRIPTION
[0023] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0024] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.
[0025] In this application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
[0026] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.
[0027] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0028] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass described in the embodiment description of the present application can be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.
[0029] The terms "first" and "second" are used only for descriptive purposes to distinguish objects such as substances from each other, and should not be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. For example, without departing from the scope of the embodiments of the present application, the first XX may also be referred to as the second XX, and similarly, the second XX may also be referred to as the first XX. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features.
[0030] In a first aspect, an embodiment of the present application provides a conductive mortar, which includes the following components in percentage by weight, based on the total weight of the conductive mortar being 100%:
[0031]
[0032] The conductive mortar provided in the embodiment of the present application is based on cement and sand and gravel, and is synergistically combined with carbon materials, fly ash and mineral powder. Not only can the carbon materials, fly ash and mineral powder be used to construct a macroscopic or microscopic conductive grid inside the cement mortar, but also the conductive grids of multiple sizes can be used to build a conductive path together to reduce the resistivity of the conductive mortar. Moreover, the coordinated use of carbon materials, fly ash and mineral powder can be used to perform secondary hydration during the cement hydration process, thereby improving the density and mechanical properties of the conductive mortar material. At the same time, the fly ash and mineral powder can also be effectively filled into the pores of the conductive mortar or concrete during the secondary hydration, thereby reducing the intrusion of chloride ions into the cement, thereby reducing OH ﹣ consumption, thus improving the ability of the conductive slurry to resist auxiliary anodic acidification.
[0033] In an embodiment, the conductive mortar includes the following components in percentage by weight: 13.3-22.5% cement, 61.5-71.3% sand, 0.06-1.18% carbon material, 1.99-8.81% fly ash, 1.99-8.81% mineral powder and 10.11-12.3% water.
[0034] In an embodiment, the carbon material is selected from expanded graphite and carbon fiber, and the mass ratio of the expanded graphite to the carbon fiber is (0.02-1.1):(0.04-0.08).
[0035] In a specific embodiment, the weight percentage of expanded graphite is 0.02-2.0%, preferably 0.02-1.1%, such as 0.02%, 0.05%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.33%, 0.4%, 0.45%, 0.5%, 0.55%, 0.6%, 0.65%, 0.7%, 0.75%, 0.8%, 0.85%, 0.9%, 1.1%, etc. Expanded graphite not only has a synergistic effect with carbon materials, fly ash, and mineral powder, but also constructs a macroscopic or microscopic conductive grid inside the cement mortar. The conductive grids of multiple sizes can jointly build a conductive path, thereby improving the conductivity of the conductive mortar, and the expanded graphite also has a large specific surface area, which is conducive to more cement hydration products to be regularly attached to its surface, and can improve the degree of cement hydration reaction. In addition, the price of expanded graphite is much lower than that of graphene and carbon nanotubes, which can significantly reduce the preparation cost of conductive mortar. The specific surface area of expanded graphite is 180-230m 2 / g, for example 180m 2 / g, 190m 2 / g, 200m 2 / g, 210m 2 / g, 220m 2 / g, 230m 2 / g, etc. As a porous material, expanded graphite is composed of a large number of network-like pore structures, and has the characteristics of strong conductivity, high surface activity and corrosion resistance. Therefore, it can form a conductive grid in the cement matrix at a relatively low addition amount, improve the conductivity of the conductive mortar, and through the expansion of the expanded graphite's rich pore structure and high thermal conductivity, the heat generated by the anode during the cathodic protection process can be quickly dispersed, which can reduce the damage of temperature stress to the surrounding concrete.
[0036] In a specific embodiment, the weight percentage of carbon fiber is 0.02-1.6%, preferably 0.04-0.08%, such as 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, etc. The carbon fiber is a short-cut carbon fiber with a carbon content of 94%-99%, a length of 5-9mm, a diameter of 5-7μm, a tensile strength of 4500-4900MPa, an elastic modulus of 230-250GPa, and a density of 1.45-1.75g / cm 3 , bulk density is 0.3g~0.5g / cm 3, the resistivity is 1.0~1.3Ω / cm. The carbon fiber has the characteristics of light weight, high strength, anisotropic softness, and can effectively improve the flexural strength of cement mortar.
[0037] In the embodiment, the weight percentage of cement is 10-25%, preferably 13.3-22.5%, such as 13.3%, 14%, 14.5%, 15%, 15.5%, 16%, 16.5%, 17%, 17.7%, 18%, 18.5%, 19%, 19.9%, 20%, 20.5%, 21%, 21.5%, 22%, 22.5%, etc. The cement is selected from silicate cement, and the specific surface area of silicate cement is 350-400m 2 / kg, for example 350m 2 / kg, 360m 2 / kg, 370m 2 / kg、380m 2 / kg, 390m 2 / kg、400m 2 / kg, silicate cement within this specific surface area range is conducive to developing the early strength of conductive paste, improving the early performance of concrete, reducing the risk of early defects in concrete, and improving the ability of concrete to resist cracking. The particle size of cement is 7 to 200 μm.
[0038] In the embodiment, the weight percentage of sand is 58-75%, preferably 61.5-71.3%, such as 61.5%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 71.3%, etc. The particle size of sand is 0.08-2mm, such as 0.08mm, 0.1mm, 0.2mm, 0.3mm, 0.4mm, 0.5mm, 0.6mm, 0.7mm, 0.8mm, 0.9mm, 1.0mm, 1.1mm, 1.2mm, 1.3mm, 1.4mm, 1.5mm, 1.6mm, 1.7mm, 1.8mm, 1.9mm, 2mm, etc. Adding sand can not only reduce the amount of cement, but also reduce the shrinkage of cement hardening.
[0039] In the embodiment, the weight percentage of fly ash is 1.0-10%, preferably 1.99-8.81%, such as 1.99%, 2.21%, 2.65%, 3.3%, 3.96%, 4.41%, 4.62%, 6.61%, 8.81%, etc. The specific surface area of fly ash is 380-420m 2 / kg, with a particle size of 1 to 100 μm. Mineral powder can refer to the product of ore crushing, such as S75 mineral powder and S95 mineral powder. The weight percentage of mineral powder is 1.0 to 10%, preferably 1.99 to 8.81%, such as 1.99%, 2.21%, 2.65%, 3.31%, 3.96%, 4.41%, 4.62%, 6.61%, 8.81%, etc. The specific surface area of mineral powder is 400 to 480 m 2 / kg, particle size is 1-100μm. The synergistic use of fly ash and mineral powder can not only be secondary hydrated during cement hydration to improve the density and mechanical properties of conductive mortar, but also can be used as conductive materials to improve the conductive properties of conductive mortar to a certain extent. In addition, fly ash and mineral powder can also effectively fill the pores of conductive mortar or concrete during secondary hydration, reduce the intrusion of chloride ions into cement, and thus reduce OH ﹣ consumption, thus improving the ability of the conductive slurry to resist auxiliary anodic acidification.
[0040] A second aspect of an embodiment of the present application provides a method for preparing a conductive mortar, comprising the following steps:
[0041] S01: providing the raw material components of the conductive mortar of the present application;
[0042] S02: dispersing the carbon material, and then drying it to obtain dispersed carbon material;
[0043] S03: performing a first mixing process on the dispersed carbon material and sand and gravel to obtain a first mixture;
[0044] S04: performing a second mixing process on the first mixture, cement, fly ash and mineral powder to obtain a second mixture;
[0045] S05: performing a third mixing process on the second mixture and water to obtain a conductive mortar.
[0046] The preparation method of the conductive mortar provided in the embodiment of the present application is as follows: the first step is to disperse the carbon material so that the carbon material is fully dispersed to obtain a dispersed carbon material; the second step is to mix the dispersed carbon material with sand and gravel to obtain a first mixture; the third step is to mix the first mixture with cement, fly ash and mineral powder to obtain a second mixture; finally, the second mixture and water are mixed for a third time to obtain the conductive mortar. The preparation method is simple and convenient, does not require large-scale instruments and equipment, and is conducive to large-scale application.
[0047] In the above step S01, the types and percentages of the components of the provided conductive mortar are as described above, and will not be repeated here to save space.
[0048] In the above step S02, the dispersion treatment includes: ultrasonic dispersion at a power of 150 to 200 W for 15 to 25 minutes. The conditions for the drying treatment include: a temperature of 60 to 70° C. and a time of 8 to 12 hours. In the embodiment, the carbon material required for preparing the specimen is placed in an ultrasonic disperser with a power of 150 to 200 W for ultrasonic dispersion for 15 to 25 minutes, and then the dispersed carbon material is placed in an oven at a temperature of 60 to 70° C. and baked for 8 to 12 hours to obtain a first carbon material.
[0049] In the above step S03, the conditions of the first mixing treatment are: stirring at a speed of 58 to 62 r / min for 25 to 35 seconds. In the embodiment, the dispersed carbon material and sand and gravel are added to the mixer and stirred at a speed of 58 to 62 r / min for 25 to 35 seconds to obtain the first mixture.
[0050] In the above step S04, the condition of the second mixing process is: stirring at a speed of 58 to 62 r / min for 50 to 70 seconds. In the embodiment, cement, fly ash and mineral powder are added to a mixer and mixed with the first mixture, and stirred at a speed of 58 to 62 r / min for 50 to 70 seconds to obtain the second mixture.
[0051] In the above step S05, the condition of the third mixing treatment is: stirring at a speed of 58 to 62 r / min for 50 to 70 seconds. In the embodiment, water is added to the mixer and mixed with the second mixture, and stirred at a speed of 58 to 62 r / min for 50 to 70 seconds to obtain the conductive mortar.
[0052] In an embodiment where the carbon material is selected from expanded graphite and carbon fiber, the preparation method of the conductive mortar comprises the following steps: providing cement, sand, expanded graphite, carbon fiber, fly ash, mineral powder and water; dispersing the carbon fiber and then drying it to obtain dispersed carbon fiber; mixing the dispersed carbon fiber with sand and gravel to obtain a first mixture; mixing the first mixture with cement, fly ash and mineral powder to obtain a second mixture; mixing the second mixture with expanded graphite to obtain a third mixture; mixing the third mixture with water to obtain conductive mortar. The mixing conditions are: stirring at a speed of 58 to 62 r / min for 50 to 70 seconds.
[0053] A third aspect of an embodiment of the present application provides a secondary auxiliary anode material, which is formed by the conductive mortar of the present application, or a conductive mortar prepared by the preparation method of the conductive mortar of the present application.
[0054] The auxiliary anode material provided in the embodiment of the present application is formed by the conductive mortar of the present application, or the conductive mortar prepared by the preparation method of the conductive mortar of the present application. Therefore, the auxiliary anode material of the present application has excellent conductive properties, mechanical properties and acid resistance.
[0055] In a specific embodiment, the conductive mortar includes the following components in percentage by weight:
[0056]
[0057] The following describes the invention in conjunction with specific embodiments.
[0058] Example 1
[0059] This embodiment provides a conductive mortar and a preparation method thereof.
[0060] The raw materials of conductive mortar include the following components:
[0061]
[0062] Among them, the silicate cement is P·O 42.5 silicate cement with a specific surface area of 330m 2 / kg, the particle size of expanded graphite is 50μm and the specific surface area is 230m 2 / g, the carbon fiber length is 9mm, the tensile strength is 4900MPa, the tensile modulus is 230GPa, the diameter is 7μm, and the density is 1.75g / cm 3 , bulk density is 0.4g / cm 3 The resistivity is 1.2Ω / cm, the particle size of sand is 0.08-2mm, and the specific surface area of fly ash is 390m 2 / kg, the specific surface area of the mineral powder is 465m 2 / kg.
[0063] The preparation method of the conductive mortar comprises the following steps:
[0064] S11: weighing the raw material components in the conductive mortar of Example 1;
[0065] S12: using an ultrasonic disperser to ultrasonically disperse the carbon fiber for 20 minutes, and then placing the dispersed carbon fiber in a 65° C. oven to dry, to obtain a first carbon fiber;
[0066] S13: adding the first carbon fiber and sand into a mixer, and stirring at a speed of 60 r / min for 30 seconds to obtain a mixture of sand and carbon fiber;
[0067] S14: adding silicate cement, fly ash and mineral powder into a mixer, mixing with the mixture of sand and carbon fiber, stirring at a speed of 60 r / min for 60 seconds to obtain a mixture of cement, fly ash, mineral powder, sand and carbon fiber;
[0068] S15: adding expanded graphite into a mixer, mixing with a mixture of cement, fly ash, mineral powder, sand and carbon fiber, stirring at a speed of 60 r / min for 60 s to obtain a mixture of expanded graphite, cement, fly ash, mineral powder, sand and carbon fiber;
[0069] S16: adding water into a mixer, mixing with the mixture of expanded graphite, cement, fly ash, mineral powder, sand and carbon fiber, stirring at a speed of 60 r / min for 60 seconds to obtain a conductive mortar.
[0070] Example 2
[0071] This embodiment provides a conductive mortar and a preparation method thereof.
[0072] The raw materials of conductive mortar include the following components:
[0073]
[0074] Among them, the silicate cement is P·O 42.5 silicate cement with a specific surface area of 330m 2 / kg, the particle size of expanded graphite is 50μm and the specific surface area is 230m 2 / g, the carbon fiber length is 9mm, the tensile strength is 4900MPa, the tensile modulus is 230GPa, the diameter is 7μm, and the density is 1.75g / cm 3 , bulk density is 0.4g / cm 3 The resistivity is 1.2Ω / cm, the particle size of sand is 0.08-2mm, and the specific surface area of fly ash is 390m 2 / kg, the specific surface area of the mineral powder is 465m 2 / kg.
[0075] The preparation method of the conductive mortar is the same as that of Example 1.
[0076] Example 3
[0077] This embodiment provides a conductive mortar and a preparation method thereof.
[0078] The raw materials of conductive mortar include the following components:
[0079]
[0080] Among them, the silicate cement is P·O 42.5 silicate cement with a specific surface area of 330m 2 / kg, the particle size of expanded graphite is 50μm and the specific surface area is 230m 2 / g, the carbon fiber length is 9mm, the tensile strength is 4900MPa, the tensile modulus is 230GPa, the diameter is 7μm, and the density is 1.75g / cm 3 , bulk density is 0.4g / cm 3 The resistivity is 1.2Ω / cm, the particle size of sand is 0.08-2mm, and the specific surface area of fly ash is 390m 2 / kg, the specific surface area of the mineral powder is 465m 2 / kg.
[0081] The preparation method of the conductive mortar is the same as that of Example 1.
[0082] Example 4
[0083] This embodiment provides a conductive mortar and a preparation method thereof.
[0084] The raw materials of conductive mortar include the following components:
[0085]
[0086]
[0087] Among them, the silicate cement is P·O 42.5 silicate cement with a specific surface area of 330m 2 / kg, the particle size of expanded graphite is 50μm and the specific surface area is 230m 2 / g, the carbon fiber length is 9mm, the tensile strength is 4900MPa, the tensile modulus is 230GPa, the diameter is 7μm, and the density is 1.75g / cm 3 , bulk density is 0.4g / cm 3 The resistivity is 1.2Ω / cm, the particle size of sand is 0.08-2mm, and the specific surface area of fly ash is 390m 2 / kg, the specific surface area of the mineral powder is 465m 2 / kg.
[0088] The preparation method of the conductive mortar is the same as that of Example 1.
[0089] Example 5
[0090] This embodiment provides a conductive mortar and a preparation method thereof.
[0091] The raw materials of conductive mortar include the following components:
[0092]
[0093] Among them, the silicate cement is P·O 42.5 silicate cement with a specific surface area of 330m 2 / kg, the particle size of expanded graphite is 50μm and the specific surface area is 230m 2 / g, the carbon fiber length is 9mm, the tensile strength is 4900MPa, the tensile modulus is 230GPa, the diameter is 7μm, and the density is 1.75g / cm 3 , bulk density is 0.4g / cm 3 The resistivity is 1.2Ω / cm, the particle size of sand is 0.08-2mm, and the specific surface area of fly ash is 390m 2 / kg, the specific surface area of the mineral powder is 465m 2 / kg.
[0094] The preparation method of the conductive mortar is the same as that of Example 1.
[0095] Example 6
[0096] This embodiment provides a conductive mortar and a preparation method thereof.
[0097] The raw materials of conductive mortar include the following components:
[0098]
[0099] Among them, the silicate cement is P·O 42.5 silicate cement with a specific surface area of 330m 2 / kg, the particle size of expanded graphite is 50μm and the specific surface area is 230m 2 / g, the carbon fiber length is 9mm, the tensile strength is 4900MPa, the tensile modulus is 230GPa, the diameter is 7μm, and the density is 1.75g / cm 3 , bulk density is 0.4g / cm 3 The resistivity is 1.2Ω / cm, the particle size of sand is 0.08-2mm, and the specific surface area of fly ash is 390m 2 / kg.
[0100] The preparation method of the conductive mortar comprises the following steps:
[0101] S11: weighing the raw material components in the conductive mortar of Example 1;
[0102] S12: using an ultrasonic disperser to ultrasonically disperse the carbon fiber for 20 minutes, and then placing the dispersed carbon fiber in a 65° C. oven to dry, to obtain a first carbon fiber;
[0103] S13: adding the first carbon fiber and sand into a mixer, and stirring at a speed of 60 r / min for 30 seconds to obtain a mixture of sand and carbon fiber;
[0104] S14: adding silicate cement and fly ash into a mixer, mixing with the mixture of sand and carbon fiber, and stirring at a speed of 60 r / min for 60 seconds to obtain a mixture of cement, fly ash, sand and carbon fiber;
[0105] S15: adding expanded graphite into a mixer, mixing with a mixture of cement, fly ash, sand and carbon fiber, and stirring at a rotation speed of 60 r / min for 60 s to obtain a mixture of expanded graphite, cement, fly ash, sand and carbon fiber;
[0106] S16: adding water into a mixer, mixing with the mixture of expanded graphite, cement, fly ash, sand and carbon fiber, and stirring at a speed of 60 r / min for 60 seconds to obtain a conductive mortar.
[0107] Example 7
[0108] This embodiment provides a conductive mortar and a preparation method thereof.
[0109] The raw materials of conductive mortar include the following components:
[0110]
[0111] Among them, the silicate cement is P·O 42.5 silicate cement with a specific surface area of 330m 2 / kg, the particle size of expanded graphite is 50μm and the specific surface area is 230m 2 / g, the carbon fiber length is 9mm, the tensile strength is 4900MPa, the tensile modulus is 230GPa, the diameter is 7μm, and the density is 1.75g / cm 3 , bulk density is 0.4g / cm 3 The resistivity is 1.2Ω / cm, the particle size of sand is 0.08-2mm, and the specific surface area of fly ash is 390m 2 / kg.
[0112] The preparation method of the conductive mortar is the same as that of Example 6.
[0113] Example 8
[0114] This embodiment provides a conductive mortar and a preparation method thereof.
[0115] The raw materials of conductive mortar include the following components:
[0116]
[0117] Among them, the silicate cement is P·O 42.5 silicate cement with a specific surface area of 330m 2 / kg, the particle size of expanded graphite is 50μm and the specific surface area is 230m 2 / g, the carbon fiber length is 9mm, the tensile strength is 4900MPa, the tensile modulus is 230GPa, the diameter is 7μm, and the density is 1.75g / cm 3 , bulk density is 0.4g / cm 3 The resistivity is 1.2Ω / cm, the particle size of sand is 0.08-2mm, and the specific surface area of fly ash is 390m 2 / kg.
[0118] The preparation method of the conductive mortar is the same as that of Example 6.
[0119] Example 9
[0120] This embodiment provides a conductive mortar and a preparation method thereof.
[0121] The raw materials of conductive mortar include the following components:
[0122]
[0123] Among them, the silicate cement is P·O 42.5 silicate cement with a specific surface area of 330m 2 / kg, the particle size of expanded graphite is 50μm and the specific surface area is 230m 2 / g, the carbon fiber length is 9mm, the tensile strength is 4900MPa, the tensile modulus is 230GPa, the diameter is 7μm, and the density is 1.75g / cm 3 , bulk density is 0.4g / cm 3 The resistivity is 1.2Ω / cm, the particle size of sand is 0.08-2mm, and the specific surface area of fly ash is 390m 2 / kg.
[0124] The preparation method of the conductive mortar is the same as that of Example 6.
[0125] Example 10
[0126] This embodiment provides a conductive mortar and a preparation method thereof.
[0127] The raw materials of conductive mortar include the following components:
[0128]
[0129]
[0130] Among them, the silicate cement is P·O 42.5 silicate cement with a specific surface area of 330m 2 / kg, the particle size of expanded graphite is 50μm and the specific surface area is 230m 2 / g, the carbon fiber length is 9mm, the tensile strength is 4900MPa, the tensile modulus is 230GPa, the diameter is 7μm, and the density is 1.75g / cm 3 , bulk density is 0.4g / cm 3 The resistivity is 1.2Ω / cm, the particle size of the sand is 0.08-2mm, and the specific surface area of the mineral powder is 465m 2 / kg.
[0131] The preparation method of the conductive mortar comprises the following steps:
[0132] S11: weighing the raw material components in the conductive mortar of Example 1;
[0133] S12: using an ultrasonic disperser to ultrasonically disperse the carbon fiber for 20 minutes, and then placing the dispersed carbon fiber in a 65° C. oven to dry, to obtain a first carbon fiber;
[0134] S13: adding the first carbon fiber and sand into a mixer, and stirring at a speed of 60 r / min for 30 seconds to obtain a mixture of sand and carbon fiber;
[0135] S14: adding silicate cement and mineral powder into a mixer, mixing with the mixture of sand and carbon fiber, stirring at a speed of 60 r / min for 60 seconds to obtain a mixture of cement, mineral powder, sand and carbon fiber;
[0136] S15: adding expanded graphite into a mixer, mixing with a mixture of cement, mineral powder, sand and carbon fiber, and stirring at a speed of 60 r / min for 60 s to obtain a mixture of expanded graphite, cement, mineral powder, sand and carbon fiber;
[0137] S16: adding water into a mixer, mixing with the mixture of expanded graphite, cement, mineral powder, sand and carbon fiber, stirring at a speed of 60 r / min for 60 seconds to obtain a conductive mortar.
[0138] Embodiment 11
[0139] This embodiment provides a conductive mortar and a preparation method thereof.
[0140] The raw materials of conductive mortar include the following components:
[0141]
[0142]
[0143] Among them, the silicate cement is P·O 42.5 silicate cement with a specific surface area of 330m 2 / kg, the particle size of expanded graphite is 50μm and the specific surface area is 230m 2 / g, the carbon fiber length is 9mm, the tensile strength is 4900MPa, the tensile modulus is 230GPa, the diameter is 7μm, and the density is 1.75g / cm 3 , bulk density is 0.4g / cm 3 The resistivity is 1.2Ω / cm, the particle size of the sand is 0.08-2mm, and the specific surface area of the mineral powder is 465m 2 / kg.
[0144] The preparation method of the conductive mortar is the same as that of Example 10.
[0145] Example 12
[0146] This embodiment provides a conductive mortar and a preparation method thereof.
[0147] The raw materials of conductive mortar include the following components:
[0148]
[0149] Among them, the silicate cement is P·O 42.5 silicate cement with a specific surface area of 330m 2 / kg, the particle size of expanded graphite is 50μm and the specific surface area is 230m 2 / g, the carbon fiber length is 9mm, the tensile strength is 4900MPa, the tensile modulus is 230GPa, the diameter is 7μm, and the density is 1.75g / cm 3 , bulk density is 0.4g / cm 3 The resistivity is 1.2Ω / cm, the particle size of the sand is 0.08-2mm, and the specific surface area of the mineral powder is 465m 2 / kg.
[0150] The preparation method of the conductive mortar is the same as that of Example 10.
[0151] Embodiment 13
[0152] This embodiment provides a conductive mortar and a preparation method thereof.
[0153] The raw materials of conductive mortar include the following components:
[0154]
[0155] Among them, the silicate cement is P·O 42.5 silicate cement with a specific surface area of 330m 2 / kg, the particle size of expanded graphite is 50μm and the specific surface area is 230m 2 / g, the carbon fiber length is 9mm, the tensile strength is 4900MPa, the tensile modulus is 230GPa, the diameter is 7μm, and the density is 1.75g / cm 3, bulk density is 0.4g / cm 3 The resistivity is 1.2Ω / cm, the particle size of the sand is 0.08-2mm, and the specific surface area of the mineral powder is 465m 2 / kg.
[0156] The preparation method of the conductive mortar is the same as that of Example 10.
[0157] Comparative Example 1
[0158] This comparative example provides a conductive mortar and a preparation method thereof.
[0159] The raw materials of conductive mortar include the following components:
[0160] Portland cement 22.2%,
[0161] Sand 66.7%,
[0162] Water 11.1%;
[0163] Among them, the silicate cement is P·O 42.5 silicate cement with a specific surface area of 330m 2 / kg, the particle size of sand is 1.5μm.
[0164] The preparation method of the conductive mortar comprises the following steps:
[0165] S1: weighing the raw material components in the conductive mortar of Comparative Example 1;
[0166] S2: adding silicate cement and sand into a mixer, and stirring at a speed of 60 r / min for 60 s to obtain a mixture of cement and sand;
[0167] S15: adding water into the mixer, mixing with the mixture of cement and sand, and stirring at a speed of 60 r / min for 60 seconds to obtain a conductive mortar.
[0168] Related performance test analysis:
[0169] 1. Using the GBT17671-1999 cement mortar strength test method (ISO method), the conductive mortars provided in Examples 1 to 13 and Comparative Example 1 were cured for 7 days and 28 days, and the compressive strength and flexural strength were tested respectively to obtain the strength at different ages. The test results are shown in Tables 1 to 2 below; wherein Table 1 shows the compressive strength of the conductive mortars provided in Examples 1 to 13 and Comparative Example 1, and Table 2 shows the flexural strength of the conductive mortars provided in Examples 1 to 13 and Comparative Example 1.
[0170] 2. The resistivity of the conductive mortars provided in Examples 1 to 13 and Comparative Example 1 was tested by a four-electrode method. Figure 2As shown, four parallel electrodes are embedded inside the test block (conductive mortar), the voltage V is measured between the two inner electrodes BC, and the current I is measured between the two outer electrodes AD. The resistance value of the BC segment can be calculated by Ohm's law, and the material resistivity value can be calculated by the resistivity calculation formula based on the BC segment distance L and the contact area A between the electrode plate and the test block. The test results are shown in Table 3 below; wherein Table 3 shows the resistivity of the conductive mortars provided in Examples 1 to 13 and Comparative Example 1 after curing for 7 days and 28 days.
[0171] 3. The conductive mortars provided in Example 1, Example 9, Example 13 and Comparative Example 1 were cured for 28 days to obtain test blocks, and then an acid resistance test was performed. The schematic diagram of the acid resistance test is shown in FIG. Figure 1 The test results are shown in Table 6; wherein Table 6 shows the resistivity change of the test blocks prepared by curing the conductive mortar provided in Example 1, Example 9, Example 13 and Comparative Example 1 for 28 days and then undergoing the acid resistance test at a constant current acceleration of 600 hours.
[0172] Table 1
[0173]
[0174] Table 2
[0175]
[0176] Table 3
[0177]
[0178] Table 4
[0179]
[0180] Table 5
[0181] Serial number Main component 1 (fly ash) Main component 2 (mineral powder) Total score Example 1 -0.46 -2.59 -0.75 Example 2 -0.70 -1.08 -0.75 Example 3 -0.66 0.96 -0.45 Example 4 -0.03 1.11 0.12 Example 5 -0.02 1.55 0.19 Example 6 0.68 0.20 0.61 Example 7 1.40 -0.46 1.15 Example 8 2.28 -0.05 1.97 Example 9 0.36 0.22 0.34 Example 10 0.19 -0.11 0.15 Embodiment 11 -0.22 0.10 -0.17 Example 12 -0.35 -0.03 -0.30 Embodiment 13 -0.59 -0.25 -0.55 Comparative Example -1.88 0.43 -1.15
[0182] Table 6
[0183]
[0184] From the results in Tables 1 to 3, it can be seen that after 28 days of curing, the compressive strength and flexural strength of the conductive mortar decrease with the increase of fly ash and mineral powder content, while the conductivity increases, indicating that fly ash and mineral powder have the effect of secondary hydration. With the addition of fly ash and mineral powder, the early mechanical properties are reduced, and with the continuous secondary hydration of fly ash and mineral powder, they will gradually increase in the later stage.
[0185] With compressive strength and resistivity as evaluation parameters, the main components (fly ash and mineral powder) of different ratios were analyzed, and the results are shown in Tables 4 to 5. It can be concluded from Tables 4 to 5 that the result of Example 1 is the best among Examples 1 to 5, the result of Example 9 is the best among Examples 6 to 9, and the result of Example 13 is the best among Examples 10 to 13. As can be seen from Table 6, the resistivity of the test blocks made of the conductive mortar provided by Example 1, Example 9, Example 13 and Comparative Example 1 after constant current acceleration for 600h are 7149Ω·cm, 8185Ω·cm, 8496Ω·cm, and 8876Ω·cm, respectively. The resistivity of the conductive mortar (test block) provided by Example 1, Example 9 and Example 13 is less than that of Comparative Example 1, indicating that fly ash and mineral powder can improve the acidification resistance of the conductive mortar, and the composite use of fly ash and mineral powder has the best effect.
[0186] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A conductive mortar, characterized in that: Taking the total weight of the conductive mortar as 100%, the conductive mortar comprises the following components in percentage by weight: Cement 10~25%, Sand 58~75%, Carbon material 0.04~3.6%, Fly ash 1.0~10%, Mineral powder 1.0~10%, Water 9~14%; Wherein, the carbon material is selected from expanded graphite and carbon fiber, the expanded graphite acts synergistically with the carbon fiber, the fly ash and the mineral powder, the fly ash and the mineral powder can be filled into the pores of the conductive mortar during secondary hydration, and the mass ratio of the expanded graphite to the carbon fiber is (0.02~1.1):(0.04~0.08).
2. The conductive mortar according to claim 1, characterized in that: The composition comprises the following weight percentages: Cement 13.3~22.5%, Sand 61.5~71.3%, Carbon material 0.06~1.18%, Fly ash 1.99~8.81%, Mineral powder 1.99~8.81%, Water 10.11~12.3%.
3. The conductive mortar according to claim 2, characterized in that: The cement is selected from Portland cement.
4. The conductive mortar according to claim 3, characterized in that: The carbon fiber has a length of 5-9 mm, a diameter of 5-7 μm, a tensile strength of 4500-4900 MPa, an elastic modulus of 230-250 GPa, and a density of 1.45-1.75 g / cm 3 , bulk density is 0.3g~0.5g / cm 3 , resistivity is 1.0~1.3Ω / cm.
5. The conductive mortar according to claim 3, characterized in that: The specific surface area of the expanded graphite is 180-230 m 2 / g; and / or The specific surface area of the silicate cement is 350-400m 2 / kg.
6. The conductive mortar according to any one of claims 3 to 5, characterized in that: The particle size of the sand is 0.08-2 mm; and / or The specific surface area of the fly ash is 380~420m 2 / kg; and / or The specific surface area of the mineral powder is 400~480m 2 / kg.
7. A method for preparing a conductive mortar, characterized in that: The following steps are involved: Providing the raw material components of the conductive mortar according to any one of claims 3 to 6; The carbon material is dispersed and then dried to obtain a dispersed carbon material; Performing a first mixing process on the dispersed carbon material and sand to obtain a first mixture; Performing a second mixing process on the first mixed material, cement, fly ash and mineral powder to obtain a second mixed material; The second mixture and water are subjected to a third mixing process to obtain a conductive mortar.
8. The preparation method according to claim 7, characterized in that: The dispersion treatment comprises: ultrasonic dispersion at a power of 150-200 W for 15-25 min; and / or The drying conditions include: a temperature of 60-70° C. and a time of 8-12 hours.
9. The preparation method according to claim 7, characterized in that: The first mixing treatment condition is: stirring at a speed of 58-62 r / min for 25-35 s; and / or The second mixing treatment condition is: stirring at a speed of 58-62 r / min for 50-70s; and / or The conditions of the third mixing treatment are: stirring at a rotation speed of 58-62 r / min for 50-70 seconds.
10. An auxiliary anode material, characterized in that: The auxiliary anode material is formed by the conductive mortar described in any one of claims 1 to 6, or the conductive mortar prepared by the method for preparing the conductive mortar described in any one of claims 7 to 9.